Bridge maintenance, safety, management, resilience and sustainability : proceedings of the Fifth International Conference on Bridge Maintenance, Safety and Management, Philadelphia, Pennsylvania, USA, 11-15 July 2010 /: proceedings of the Fifth International Conference on Bridge Maintenance, Safety and Management, Philadelphia, Pennsylvania, USA, 11-15 July 2010. ([2012]) - Unknown
No abstract available